Maternal critical care: what can we learn from patient experience? A qualitative study - Lisa Hinton; Louise Locock; Marian Knight (2015)
For every maternal death, nine women develop severe maternal morbidity. Many of those women will need care in an intensive care unit (ICU) or high dependency unit (HDU). Critical care in the context of pregnancy poses distinct issues for staff and patients, for example, with breastfeeding support and separation from the newborn. This study aimed to understand the experiences of women who experience a maternal near miss and require critical care after childbirth.Women and some partners from across the UK were interviewed as part of a study of experiences of near-miss maternal morbidity.A qualitative study, using semistructured interviews.A maximum variation sample was recruited of 35 women and 11 partners of women who had experienced a severe maternal illness, which without urgent medical attention would have led to her death. 18 of the women were admitted to ICU or HDU.The findings are presented in three themes: being in critical care; being a new mother in critical care; transfer and follow-up after critical care. The study highlights the shock of requiring critical care for new mothers and the gulf between their expectations of birth and what actually happened; the devastation of being separated from their baby, how valuable access to their newborn was, if possible, and the importance of breast feeding; the difficulties of transfer and the need for more support; the value of follow-up and outreach to this population of critical care patients.While uncommon, critical illness in pregnancy can be devastating for new mothers and presents a challenge for critical care and maternity staff. This study provides insights into these challenges and recommendations for overcoming them drawn from patient experiences.